Bonaparte and the British : prints and propaganda in the age of Napoleon ; [published to accompany the exhibition Bonaparte and the British: prints and propaganda in the age of Napoleon at the British Museum from 5 February to 16 August 2015] - Clayton, Tim (British Museum Press, 2015)
Not only was Waterloo one of the most decisive battles ever fought, it was also a crucial event in European history, ending over 20 years of conflict and bringing to his knees one of Europe's most challenging figures - Napoleon Bonaparte. Accompanying a major British Museum exhibition to mark the 200th anniversary of the battle of Waterloo, this intriguing book shows through contemporary prints how Bonaparte was seen from across the English Channel, where hostile propaganda was tempered by admiration for his military and administrative talents. With stunning illustrations showing the intricately detailed prints in full colour this book brings to life a key period in European history. Exhibition: British Museum, London, U.K., February 5-August 16, 2015